To Stress or Not to Stress: A Question of Models. Issue 1 (5th January 2015) - Gray, J. Megan; Chaouloff, Francis; Hill, Matthew N.
Abstract: Stress research is a rapidly evolving field that encompasses numerous disciplines ranging from neuroscience to metabolism. With many new researchers migrating into the field, navigating the hows and whys of specific research questions can sometimes be enigmatic given the availability of so many models in the stress field. Additionally, as with every field, there are many seemingly minor experimental details that can have dramatic influences on data interpretation, although many of these are unknown to those not familiar with the field. The aim of this overview is to provide some suggestions and points to guide researchers moving into the stress field and highlight relevant methodological points that they should consider when choosing a model for stress and deciding how to structure a study. We briefly provide a primer on the basics of endpoint measurements in the stress field, factors to consider when choosing a model for acute stress, the difference between repeated and chronic stress, and importantly, influencing variables that modulate endpoints of analysis in stress work. © 2015 by John Wiley & Sons, Inc.